Politeness of front counter staff of Malaysian Private Hospitals - Kuang, Ching Hei; David, Maya Khemlani; Lau, Su Kia (Penerbit UKM, 2013)

(untitled)
Politeness is an important social element in the Malaysian society and it is gauged by the way people behave towards each other during interactions. In this context, politeness is taken to mean good manners such as greeting, acknowledging and thanking others. Taking the cue from the Malaysian government which emphasizes on showing good manners, this paper examines the public transactions of front counter staff and patients in nine Malaysian private hospitals. Focus was given to the use of openings and closings in 158 transactions which were extracted over a period of three months via close observations which were allowed by the gatekeepers manning the front counters. Data were then orthographically transcribed. Brown and Levinson’s (1987) notion of politeness and the Malaysian concept of good manners such as greeting and thanking were applied as a framework. Our analysis indicates that front counter staff in private hospitals employed more impolite openings but at the end of the transactions, they used more polite closings. A closer analysis of the data indicates that these polite closings were often given in response to patients’ initiations. Although our findings are small in comparison, we believe they will benefit researchers of communication, curriculum designers and practitioners as these findings clearly indicate that there is a need for professional communication skills to be taught and implemented in service industries.